Sustained Hippocampal Synaptic Pathophysiology Following Single and Repeated Closed-Head Concussive Impacts - McDaid, John; Briggs, Clark A.; Barrington, Nikki M.; Peterson, Daniel A.; Kozlowski, Dorothy A.; Stutzmann, Grace E. (Frontiers in Cellular Neuroscience, 2021)
Traumatic brain injury (TBI), and related diseases such as chronic traumatic encephalopathy (CTE) and Alzheimer’s (AD), are of increasing concern in part due to enhanced awareness of their long-term neurological effects on memory and behavior. Repeated concussions, vs. single concussions, have been shown to result in worsened and sustained symptoms including impaired cognition and histopathology. To assess and compare the persistent effects of single or repeated concussive impacts on mediators of memory encoding such as synaptic transmission, plasticity, and cellular Ca2+ signaling, a closed-head controlled cortical impact (CCI) approach was used which closely replicates the mode of injury in clinical cases. Adult male rats received a sham procedure, a single impact, or three successive impacts at 48-hour intervals. After 30 days, hippocampal slices were prepared for electrophysiological recordings and 2-photon Ca2+ imaging, or fixed and immunostained for pathogenic phospho-tau species. In both concussion groups, hippocampal circuits showed hyper-excitable synaptic responsivity upon Schaffer collateral stimulation compared to sham animals, indicating sustained defects in hippocampal circuitry. This was not accompanied by sustained LTP deficits, but resting Ca2+ levels and voltage-gated Ca2+ signals were elevated in both concussion groups, while ryanodine receptor-evoked Ca2+ responses decreased with repeat concussions. Furthermore, pathogenic phospho-tau staining was progressively elevated in both concussion groups, with spreading beyond the hemisphere of injury, consistent with CTE. Thus, single and repeated concussions lead to a persistent upregulation of excitatory hippocampal synapses, possibly through changes in postsynaptic Ca2+ signaling/regulation, which may contribute to histopathology and detrimental long-term cognitive symptoms.